AST-120 (Spherical Carbon Adsorbent) in the Treatment of Perianal Fistulae in Mild-to-Moderate Crohn's Disease: FHAST-1, a Phase 3, Multicenter, Placebo-controlled Study. Issue 5 (1st April 2014) - Reinisch, Walter; Travis, Simon; Hanauer, Stephen; Wang, Hong; Shara, Nawar; Harris, M. Scott
Abstract : Background: AST-120 (spherical carbon adsorbent) was previously reported to be effective for perianal fistula healing in Japanese patients with mild-to-moderate Crohn's disease. Methods: To evaluate the efficacy and safety of AST-120 in a Western population, a phase 3, multicenter, randomized, double-blind, placebo-controlled, study (FHAST-1) was conducted in adult patients with at least 1 draining perianal fistula and a Crohn's disease activity index <400. Patients received either AST-120 or matching placebo at a dose of 2 g 3 times daily for 8 weeks. The primary endpoint was the proportion of patients with treatment success, defined as a 50% reduction in the number of draining fistulae, at both weeks 4 and 8. A multivariate model was generated to assess covariates for treatment success among baseline variables. Results: Two hundred forty-nine patients were randomized (AST-120; n = 122; placebo, n = 127). The proportions of patients achieving the primary endpoint were no different between treatment groups (13.9% versus 16.5%, P = 0.6). No differences in fistula response were noted at week 4 (23.0% versus 25.2%, P = 0.77) or week 8 (27.0 versus 34.6%, P = 0.22). Serum C-reactive protein concentrations >0.6 mg/dL and Crohn's disease activity index scores >151 at baseline were associated with a reduced likelihood of treatment success (odds ratio, 0.40; confidence interval, 0.19–0.87; P = 0.02; and odds ratio, 0.45; confidence interval, 0.21–0.97; P = 0.04, respectively). Conclusions: In this largest placebo-controlled trial to date to evaluate the impact of a therapeutic agent on perianal fistulae in Crohn's disease, the efficacy of AST-120 could not be confirmed. An inverse relationship was observed between both inflammatory and clinical disease activity and fistula response.